The assessment of the level of knowledge about dietary fibre among the portuguese population - Guiné, Raquel (2016)
The aim of this work was to assess the degree of knowledge about dietary fibre (DF), as influenced by factors such as age, gender, level of education and living environment. For this, a descriptive cross- sectional study was undertaken by means of a questionnaire and the total number of respondents was 382. The results revealed that the participants had a not satisfying global level of knowledge (3.59 ± 0.64, on a scale from 1 to 5). The overall knowledge was found lower for young adults aged 19 to 30 years, when compared to adults aged over 31 and up to 65 years, being this difference statistically significant (p=0.030). However, no statistical significant differences were found between genders, levels of education or living environments. The low level of knowledge demonstrated by the enquired alerts for the need to plan some additional actions to further inform the Portuguese population about dietary fibre.